Analysis of a series resonant AC/DC converter with integral cycle mode control for high frequency AC distribution systems - Cendoya, Marcelo Gustavo (2020)
The study of a resonant AC/DC converter, thought for high frequency sinusoidal AC power distribution systems, is performed in this article. The control switch is commuted at the resonant current zero crossings, staying closed (or open) for a certain number of complete cycles. This commutation strategy, known as “integral cycle mode control”, gives soft-switching which improves efficiency, minimizes EMI and increases reliability and converter life span. Also, the input current has a low THD and a good power factor. A suitable scheme to control the converter is proposed. It consists of an internal loop based on sliding mode techniques, for regulating the amplitude of the resonant current, and an external PI loop with an added feed-forward action, that sets the DC output voltage. The main objective is minimizing the disturbing effect that variations in the AC bus voltage and load consumption have over the DC output voltage. For the design of the control laws, a model expressed in terms of rectified and averaged sinusoidal variables is employed. Computer simulations have been performed, considering typical surrounding conditions for this kind of application. The obtained results show that the converter DC output voltage stay always close to its reference value, presenting good rejection against the aforementioned disturbances.